PIERRE LOUYS Y LAS IRONÍAS DEL AMOR: DANAË OU LE MALHEUR - Isabel Urzaiz Ramírez de Haro (Anales de Filología Francesa)
This article analyses a short story by Pierre Louÿs (1870-1925), Danaë ou le malheur, where the deceits of romantic, idealised love are ironically portrayed. Ultimately, the position of the blind lover, willing to sacrifice present joys in order to wait for future salvation at the hands of so-called true love, is implicitly compared to that of the credulous reader, eager to find entertainment in what he expects to be the dramatic, final twist in the tale, but overlooking the exquisite details of a marvellously written, if slightly disconcerting, tale.